Labour market attachment dynamics in patients with concussion: a Danish nationwide register-based cohort study - Heidi Jeannet Graff; Volkert Siersma; Anne Møller; Frans Boch Waldorff; Frederikke Agerbo Modin; Hana Malá Rytter (BMC, 2023)
Abstract Background Concussion may lead to persisting post-concussive symptoms affecting work ability and employment. This study examined the transitions between labour market states an individual can experience after the acute phase of concussion. The aim was to describe the incidence of favourable and adverse transitions between different labour market states (e.g., employment, sick leave) in relation to socioeconomic and health characteristics in individuals with concussion relative to matched controls. Methods This Danish nationwide register-based cohort study extracted 18-60-year-old individuals between 2003-2007 with concussion from the Danish National Patient Register (ICD-10 S06.0). Controls were matched on age, sex, and municipality. Patients and controls were followed for 5 years starting three months after injury. Exclusion criteria were neurological injuries and unavailability to the labour market in the inclusion period (2003-2007) and 5-years before injury (1998-2002). Labour market states were defined from transfer income data in the Danish Register for Evaluation of Marginalization. Incidence rates of transitions between these labour market states were analysed in multistate models. Transitions were bundled in favourable and adverse transitions between labour market states and the difference in incidence rates between individuals with concussion relative to matched controls were assessed with hazard ratios from Cox regression models. Results Persons with concussion (n = 15.580) had a lower incidence of favourable transitions (HR 0.88, CI 0.86-0.90) and a higher incidence of adverse transitions (HR 1.30, CI 1.27-1.35), relative to matched controls (n = 16.377). The effect of concussion differed depending on health and socioeconomic characteristics. Notably, individuals between 30-39 years (HR 0.83, CI 0.79-0.87), individuals with high-income (200.000-300.000 DKK) (HR 0.83, CI 0.80-0.87), and wage earners with management experience (HR 0.60, CI 0.44-0.81) had a markedly lower incidence of favourable transitions compared to controls. Additionally, individuals with high income also had a higher incidence of adverse transitions (HR 1.46, CI 1.34-1.58) compared to controls. Conclusions Concussion was associated with enhanced risk of adverse transitions between labour market states and lower occurrence of favourable transitions, indicating work disability, potentially due to persistent post-concussive symptoms. Some age groups, individuals with high income, and employees with management experience may be more affected.